Les Grandes Chroniques de France, mss. L.V.47 e L.II.8 della Biblioteca Nazionale Universitaria di Torino: studio storico-artistico di un manoscritto danneggiato nell’incendio del 1904 - Saroni, Giovanna (Scrineum, 2020)
The article centres on a manuscript copy of the Grandes Chroniques de France from the book collections of the House of Savoy, which was seriously damaged in the fire that struck the Biblioteca Nazionale Universitaria of Turin in January 1904. The author attempts to reconstruct the original manuscript by starting from the ancient catalogues of the library, and she focuses on its iconographical cycle, which can be attributed to the second artist of ms. Français 823 of the Bibliothèque nationale of Paris, who, it has been hypothesised but not unanimously, could be the illuminator Pierre or Perrin Remiet, quoted in various Parisian documents dating between 1386 and 1428. The article focuses on the manuscripts which were produced by this workshop, attempting where possible to identify their first owners. What emerges is the image of a relatively prolific workshop of illuminators, specializing in the decoration of texts with a profane content written in the vernacular, destined for clients from different levels of society, among whom some of the greatest bibliophiles of the time, first and foremost the duke Jean de Berry. The article ends with some considerations on the original history of the Grandes Chroniques of Turin, which may have entered the Savoy collections as early as the late medieval period.